Artemether-lumefantrine treatment failure of uncomplicated Plasmodium falciparum malaria in travellers coming from Angola and Mozambique. (September 2021) - Silva-Pinto, André; Domingos, João; Cardoso, Margarida; Reis, Ana; Benavente, Ernest Diez; Caldas, João Paulo; Conceição, Cláudia; Toscano, Cristina; Baptista-Fernandes, Teresa; Clark, Taane G.; Mansinho, Kamal; Campino, Susana; et al.
HIGHLIGHTS: Artemether-lumefantrine (AL) treatment failure of imported malaria in Portugal AL treatment failure in the presence of wild-type pfk13 and pfmdr1 Is the standard 3-day course of AL sufficient to ensure parasite clearance? AL increasing treatment failures urges closer immediate follow up of malaria patients ABSTRACT: The failure of artemisinin combination therapy (ACT) in malaria patients returning from endemic regions may be driven by parasite resistance to this treatment. ACT is used globally as the first-line treatment for Plasmodium falciparum malaria. However, artemisinin-resistant strains of P. falciparum have emerged and spread across Southeast Asia, with the risk of reaching high malaria burden regions in Africa and elsewhere. Here, we report on two malaria imported cases from Africa with possible parasite resistance to the ACT artemether-lumefantrine (AL). Case presentation: Two middle-aged males returning from Angola and Mozambique developed malaria symptoms in Portugal, where they were diagnosed and received treatment with AL as hospital inpatients. After apparent cure and discharge from hospital, these individuals returned to hospital showing signs of late clinical failure. Molecular analysis was performed across a number of drug resistance associated genes. No evidence of pfk13 -mediated artemisinin resistance was found. Both subjects had complete parasite clearance after treatment with non-ACT antimalarials. Conclusion: Our case-studies highlights the need for close monitoring of signs of unsatisfactory antimalarial efficacy among AL treated patients and the possible implication of other genes or mutations in the parasite response to ACTs.